2019
DOI: 10.1111/jspn.12270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a posttonsillectomy management program using a mobile instant messenger on parents’ knowledge and anxiety, and their children's compliance, bleeding, and pain

Abstract: Purpose Pediatric tonsillectomy is a highly common surgery for children. The inclusion of tonsillectomy in the diagnosis‐related group payment system in Korea has resulted in a shorter hospital stay for patients who undergo tonsillectomy. This, in turn, provides parents with additional caregiver roles in the home. Objectives This study aimed to investigate the effects of a postdischarge management program (PDMP) using Mobile Instant Messenger (MIM) on parents’ knowledge and state anxiety about postoperative ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Telenursing is delivering nursing care and conducting nursing practice by using technology. There was some evidence related to application of telenursing in nursing practice and reported that it could be used for consultation, education, monitoring, and the evaluation of health care outcomes (10,5) .…”
Section: Australian Confederation Of Pediatric Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Telenursing is delivering nursing care and conducting nursing practice by using technology. There was some evidence related to application of telenursing in nursing practice and reported that it could be used for consultation, education, monitoring, and the evaluation of health care outcomes (10,5) .…”
Section: Australian Confederation Of Pediatric Andmentioning
confidence: 99%
“…This new field of nurses' activities has expanded in many countries (13) .The innovation of telenursing technologies is diverse, such as mobile phones, smart phones, computers, Internet, videoconference, and telemonitoring equipment (14,15) . Kim and Yu (5) Telenursing may support general nursing, which is facing a shortage of nurses nowadays, and the demand for telenurses is worldwide. To meet the patients' needs and with the current nursing shortage, many homecare agencies have to look at innovative ways to care for the increasing numbers of patients (16) .…”
Section: Australian Confederation Of Pediatric Andmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Another study investigated the utility of a mobile instant messenger in the postoperative management of pediatric tonsillectomy and found this to improve compliance with at-home care instructions. 66 …”
Section: Resultsmentioning
confidence: 99%
“…Regardless of subspecialty, studies have shown that these tools can enhance diagnostic accuracy, management, and follow-up efficacy, as well as facilitate more efficient communication and improve adherence to medications. 27 , 30 - 34 , 66 , 69 , 125 , 126 Tele-rehabilitation has been applied in most subspecialities. One study investigated the feasibility of providing therapy via a mobile app, 58 pointing toward the likely future applications of many tele-rehabilitation services.…”
Section: Discussionmentioning
confidence: 99%